Association between serum selenium concentrations and learning disability in a nationally representative sample of U.S. children. (3rd July 2022) - Liu, Buyun; Xu, Guifeng; Yang, Wenhan; Strathearn, Lane; Snetselaar, Linda G.; Bao, Wei
ABSTRACT: Background: Oxidative stress has been implicated in the pathogenesis of neurodevelopmental disorders. As an anti-oxidative agent, selenium plays an important role in human health. However, the relationship between selenium status and learning disability (LD), a common neurodevelopmental disorder, is unknown. Objective: To examine the association between serum selenium concentrations and learning disability. Design: Nationwide, population-based, cross-sectional study. Participants/setting: Children aged 4–11 years who have available data on serum selenium concentrations and LD ( N  = 1, 076) from the U.S. National Health and Nutrition Examination Survey 1999–2000. Exposure: Serum selenium levels were measured using atomic absorption spectrometry. Main outcome measures: Diagnosis of LD was reported by the children's parents. Statistical analyses performed: Logistic regression models with survey weights were conducted adjusting for age, race/ethnicity, family income, total energy intake, body mass index, and serum cotinine levels. Results: In this study, 8.2% (95% confidence interval [CI] 5.2%–11.2%) of children had a diagnosis of LD. Serum selenium concentration was lower among children with LD than those without LD (geometric mean ± standard error, 107.7 ± 2.7 ng/mL vs. 112.8 ± 1.0 ng/mL, P for difference = 0.08). The adjusted odds ratio (OR) of LD comparing the highest with lowest tertile of serum selenium concentrations was 0.39 (95% CI 0.19–0.82). Each 10 ng/mL increment in serum selenium concentrations was associated with 31% (OR 0.69, 95% CI 0.51–0.93) lower odds of LD. Conclusions: Higher serum selenium concentration was associated with a lower risk of LD in U.S. children. The causal relationship between selenium and LD and the underlying mechanisms warrant further investigation.